R&D and Innovation Management in the Brazilian Electricity Sector: the Regulatory Constraint - Denile Cominato Boer; Sergio Luiz Monteiro Salles-Filho; Adriana Bin (Journal of Technology Management & Innovation, 2014)
In 2000 it became mandatory to the Brazilian electricity companies to invest in research, development and innovation (RDI). These investments are performed by firms and regulated by the Brazilian Electricity Regulatory Agency (ANEEL). Since then companies have sought ways to cope with this obligation creating internal structures and managerial processes. This article presents the evolution of RDI management routines and organizational models based on a multiple-case study conducted between 2011 and 2012 with seven companies that represent about 27% of the total RDI investment performed in the period of 2008 to 2013. The research showed that firms created minimalist management and organizational structures to handle with the RDI enforcement. Companies have been much more concerned with the regulatory risk (the risk of non-accomplishment with the obligations) than to any strategic use of RDI effort since the legal framework is based on punishment rather than in stimulus.